Usefulness of sonourethrography for penile abscess as a result of xanthogranulomatous granuloma in the corpus cavernosum of an adult: A case report. (26th May 2015) - Minagawa, Tomonori; Kato, Haruaki; Ogawa, Teruyuki; Uehara, Takeshi; Ishizuka, Osamu
Abstract A 75‐year‐old man presented with a 4‐month history of a swollen and painful penis. Computed tomography showed a round‐shaped mass measuring 3 × 2 cm in the corpus cavernosum. Percutaneous drainage of the penile mass was carried out and a course of antibiotics was prescribed. Viral, fungal and selective bacterial cultures were negative. Total penectomy and urethroperineal fistula formation were carried out because of penile pain. Histopathological diagnosis was xanthogranulomatous granuloma of the corpus cavernosum. Before surgery, sonourethrography was carried out under general anesthesia. Sonourethrography is an infrequently used modality to observe the male urethra under urinary micturition or injection of saline. We previously reported modified sonourethrography with retrograde jelly injection. In the present case, sonourethrography successfully showed the damaged and deformed urethra including the abscess cavity and fistula. Although xanthogranulomatous granuloma is rare, the findings reported here showed the usefulness of sonourethrography for morphological evaluation of the male urethra.